Albania, an ex-communist country during the transition period: Problems and challenges - Vasilika Kume; Shyqyri Llaci (Journal for East European Management Studies, 2000)
This paper intends to give a brief history of the Albanian Economy before and during the transition period, to analyze the transformation of Albanian Society toward an economy based on private property and the free initiative of free people, and to highlight some of the problems and challenges Albania is currently facing. The aim of this article is to tell what could be some of the ways for a fast recovery and steady development of our country. – – In diesem Artikel wird die Geschichte der albanischen Ökonomie vor und während der Übergangsperiode kurz dargestellt. Damit verbunden ist die Analyse der Umwandlung der albanischen Gesellschaft hin zu einer Ökonomie, die auf Privateigentum und der freien Initiative freier Menschen beruht, wobei einige Probleme und Herausforderungen aufgezeigt werden, die in Albanien aktuell sind. In diesem Artikel sollen einige der Wege, die zu einer schnellen Erholung und nachhaltigen Entwicklung unseres Landes führen könnten, gewiesen werden.
Keywords: 650